"Alas, Short is the Joy of Life!" Elamite Funerary Practice in the First Half of the First Millennium BCE - Wicks, Yasmina (Culture and History of the Ancient Near East, 2019)
Recent scholarship has begun to unveil the culturally rich and dynamic landscape of southwest Iran during the first half of the first millennium BCE (aka the Neo-Elamite period) and its significance as the incubation ground for the Persian Empire. In Profiling Death. Neo-Elamite Mortuary Practices, Afterlife Beliefs, and Entanglements with Ancestors , Yasmina Wicks continues the investigation of this critical epoch from the perspective of the mortuary record, bringing forth fascinating clues as to the ritual practices, beliefs, social structures and individual identities of Elam's lowland and highland inhabitants. Enmeshed with its neighbours, yet in many ways culturally distinct, Elam receives its due treatment here as a core component of the ancient Near East.